An improved methodology for collaborative construction of reusable, localized, and shareable ontology - Sattar, A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Interlocking Institutional Worlds (IWs) is a concept explaining the need to interoperate between institutions (or players), to solve problems of common interest in a given domain. Managing knowledge in the IWs domain is complex; however, promoting knowledge sharing based on standards and common terms agreeable to all players is essential and is something that must be established. In this context, ontologies, as a conceptual tool and a key component of knowledge-based systems, have been used by organizations for effective knowledge management, better decision-making, and interoperability among diverse institutions of an IWs domain. The development of ontology involves structural and logical complexity, and requires a well-designed, mature, and widely accepted methodology, to ensure its reliability. Many methodologies for ontology development have been proposed by several researchers; however, most of the developed methodologies have not included several important phases. Furthermore, several methodologies have not provided the complete details of the techniques and activities involved in the ontology construction process. Fewer details make it difficult to follow a methodology for designing ontologies. This study aims to compare existing methodologies based on sixteen important criteria and proposes an improved methodology for ontology development for IWs domains. The proposed methodology has included several important phases such as the Estimation of Human Resources, Re-engineering and Reusing of Resources, Collaborative Ontology Construction, the Conceptualization of both Endurants and Perdurants, Localization of an Ontology, Ontology Integration and Merging, Support for Interoperability, Versioning of an Ontology, and Ontology Population. The proposed methodology has been applied to design an OntoWM domain ontology for the Waste Management (WM) domain. The evaluation of the proposed methodology has been made by utilizing the designed OntoWM domain ontology in an ontology-based web application called SmartBinAnalytics. SmartBinAnalytics has been built using OntoWM, Java Server Pages (JSP), Jena Application Programming Interface (API), and MySQL. The proposed methodology can be used for the construction of domain ontologies in any IWs domain. CCBY